ELDOC - Design of Electric Dolly Camera for Video Recording Using the Omni-Direction Wheel - Gramandha Wega Intyanto; Ahmad Arbi Trihatmojo; Dwi Ariani Finda Yuniarti; Anggara Trisna Nugraha (Walisongo Journal of Information Technology, 2023)
The dolly camera has function as a regulator of camera movement in making video productions such as films. The movement system on the dolly camera uses the thrust of humans and the running track rail for its movement. The process of preparing the dolly camera also requires a long process, such as assembling the dolly camera and then installing the track, etc. In this case study, we conducted research that designed an electric vehicle to carry a camera but with a simple way of working such as moving without rails and can be controlled with a mobile android. We named this robot vehicle ELDOC: Electric Dolly Camera which uses a four Omni-direction wheels system in the flexibility of direction and motion for taking videos and pictures. Contributions to the design of ELDOC in addition to the multimedia/cinematography field can also be used in the medical field as a monitoring tool for patient activities in isolation or ICU room with a mobile android from different rooms. In the results of the process running on the motor, we take error data from the calculation speed and measurement speed, wherein the duty circle is 19.60%, 38.50%, 58.8%, 78.66%, and the average error is 0,08. The stability level of the ELDOC when carrying the camera is stable but has vibrations or oscillations. The results of the data orientation (gyroscope) show the total average of the three samples Y (Roll) orientation is 0.6°/s and X (Pitch) orientation is 0.18°/s.